Evaluation of psychological stress, cortisol awakening response, and heart rate variability in patients with chronic prostatitis/chronic pelvic pain syndrome complicated by lower urinary tract symptoms and erectile dysfunction - Bai, Jian; Gu, Longjie; Chen, Yinwei; Liu, Xiaming; Yang, Jun; Li, Mingchao; Dong, Xiyuan; Yang, Shulin; Huang, Bo; Wang, Tao; Jin, Lei; Liu, Jihong; et al. (Frontiers in Psychology, 2022)
Background: Mental stress and imbalance of its two neural stress systems, the HPA axis and the ANS, are associated with CP/CPPS and ED. However, the comprehensive analyses of psychological stress and stress systems are under-investigated, particularly in CP/CPPS patients complicated by LUTS and ED. Materials and Methods: Participants were 95 patients in CP/CPPS+ED group, 290 patients in CP/CPPS group, 124 patients in ED group and 52 healthy men in control group. 25 subjects per group were randomly selected for further investigating the changes of the HPA axis and ANS. Saliva samples were taken on 3 consecutive days at 8 specific times with strict reference to time of morning awakening for evaluation of free cortisol. HRV as marker of the ANS was measured using 24h electrocardiography, and time- and frequency-domain variables were analyzed. Results: The BAI and SCL-90 scores were significantly higher in the CP/CPPS+ED, CP/CPPS and ED groups compared with the control group. The PSS scores of both groups with ED were significantly higher than the control group. Compared with the CP/CPPS group, the differences of PSS, SCL-90 and TAPT scores were statistically significant in CP/CPPS+ED patients. The IPSS scores were shown to have significantly positive correlations with BAI, PSS and SCL-90 in the CP/CPPS patients. However, in the ED patients, the IIEF-5 scores were shown to have significantly negative correlations with BAI, PSS, SCL-90 and quality of life score in NIH-CPSI. CAR parameters and diurnal cortisol levels did not significantly vary between the four groups. In the frequency domain analysis, LF was significantly lower in ED patients when compared with controls, HF power was significantly higher in healthy controls compared to patients with ED , CP/CPPS and CP/CPPS+ED, and the CP/CPPS+ED group had significantly higher LF/HF ratio than the control group. Conclusion: CP/CPPS and ED patients score exceedingly high on most psychosocial variables. The severity of LUTS and ED positively correlates with the severity of psychological stress. Our findings also suggest that increased sympathetic and decreased parasympathetic nervous system activity is associated with ED and LUTS in CP/CPPS, whereas HPA axis activity is not.